A methodology to obtain traceability for internal and external measurements of Inconel 718 components by means of XRCT. (June 2021) - Ortega, Naiara; Plaza, Soraya; Pascual, Alejandro; Holgado, Ibon; Lamikiz, Aitzol
Abstract: There is undoubtedly an increasing trend towards the use of XRCT as a dimensional metrology tool, driven mainly by the proliferation of complex and hollow parts in the industry. While this technology is suitable for qualitative analysis, a consistent methodology is nevertheless needed, so that XRCT could be considered an accurate and reliable technology for carrying out dimensional and geometrical quantitative analysis. Therefore, the main aim of this approach is to develop a methodology for a traceable measurement of external and internal features. To do it, each measurement is associated with its corresponding task-specific uncertainty estimation by an adapted substitution approach, and thus providing a novel traceable XRCT measurement methodology. The proposed methodology is based on using a reference object related to the workpiece to measure external and internal features of an Inconel 718 component by means of XRCT. In both cases, traceability is guaranteed by the use of conventional dimensional metrology instruments. Results show that wall thicknesses can be accurately measured with errors below 2% for all the cases studied (wall thicknesses from 0.957 to 2.648 mm). As internal measurements are more prone to suffer artifacts, inner diameter deviations from nominal values are from 0.3% in the best XRCT conditions to 19.5% in the worst conditions. With the aim of providing a better scientific understanding of the measurement by means of XRCT, further tests were carried out. CT parameters influence on the beam hardening effect and on the surface definition was studied. Results show that the traceability is assured when the proposed methodology is used.